Intravascular lithotripsy for the treatment of calcified coronary artery disease: A case series - Julian Wei Ee, Tong; En Ze, Chan; Bui Khiong, Chung; Hwei Sung, Ling; How Kiat, Khor; Andy Tze Yang, Ko; Kit How, Chiang; Lai Kuan, Leong; Ing Xiang, Pang; Cheng Foong, Cheah; Esteban Yu Hern, Chin; Francis Eng Pbeng, Shu; et al. (Wolters Kluwer Health, Inc, 2025)
Severe coronary artery calcification poses major challenges to percutaneous coronary intervention, often limiting stent expansion and procedural success. The Sonico-CX intravascular lithotripsy (IVL) system is a novel calcium-modification device designed to fracture calcified plaques using acoustic shockwaves. We present a case series of twenty-one patients with balloon-undilatable, severely calcified lesions treated with this new IVL system. All procedures were performed by experienced interventional cardiologists between April and August 2024. Adjunctive non-compliant and scoring balloons were used, and four cases required rotational atherectomy to facilitate IVL delivery. IVL achieved a high procedural success rate (90.5%) with no intra-procedural complications or in-hospital and 30-day major adverse cardiovascular events. The use of IVL enabled effective drug-coated balloon therapy in 85.7% of cases, reducing the need for stent implantation. This case series highlights the safety and efficacy of a novel IVL system and its potential to simplify complex percutaneous coronary intervention by providing effective lesion preparation in heavily calcified coronary disease